The Role of P2TP2A for Women Victims of Domestic Violence as a Form of Realization of Human Rights Enforcement - Erlitha Dewi Ramadhiana; Jum Anggriani (Jurnal Smart Hukum (JSH), 2025)
This research analyzes the role of Integrated Service Centers for Women and Children Empowerment (P2TP2A) towards women victims of domestic violence as a manifestation of human rights enforcement in Indonesia. Using normative juridical method, this study examines the juridical construction of P2TP2A based on the hierarchy of legislation and international human rights instruments. The findings indicate that although P2TP2A has a strong legal foundation from the 1945 Constitution to Ministry Regulation No. 5/2010, its implementation faces significant paradox between normative ideality and practical reality. Of 514 regencies/cities, only 398 have P2TP2A with varying operational readiness, while 67% of victims are unaware of this institution's existence. Determinant factors affecting effectiveness include institutional capacity disparities, limited competent human resources, suboptimal inter-stakeholder coordination, and persistent patriarchal culture. The research formulates a holistic capacity strengthening model based on four pillars: human resource competency standardization, coordination optimization, infrastructure strengthening, and outcome-based monitoring systems to realize sustainable victim protection.